A Cloud Point Extraction Approach Developed for Analyzing Pesticides Prometryne and Isoproturon from Multi‐media. Issue 5 (18th January 2013) - Tan, Jian Hua; Jin, She Feng; Yang, Hong
Abstract A new analytic methodology based on the cloud point extraction coupled with HPLC (CPE‐HPLC) was developed and successfully applied to determination of the pesticides isoproturon (IPU) and prometryne (PRO) from multi‐media (contaminated water, soil, and food vegetable). Several non‐ionic surfactants including poly ethylene glycol 6000 (PEG‐6000), TritonX‐114, and Triton X‐100 were comparatively analyzed as extraction solvents. Other parameters such as surfactant concentration, ionic strength, and equilibration temperature, and duration were also investigated. The optimal conditions for CPE were presented with 2.4% w/v PEG‐6000, 11% w/v Na2SO4 and heating assistance at 50°C for 25 min. The calibration curves for the two analytes were linear ranging from 0.001 to 10.0 mg L−1, with correlation coefficients being 0.99 determined by a HPLC–UV detector. Under the condition, the average recoveries were 85.4–90.6% for water, 84.4–92.7% for soil, and 84.4–92.1% for vegetable. Thus, the method presented here was proved to be rapid, efficient, and green for extraction and determination of isoproturon and prometryne residues from food and multi‐environmental media.